Sepsis - Kumar, Vijay (IntechOpen, 2017)
The book entitled Sepsis will provide a great and up-to-date information in this field to students and researchers involved in sepsis research with its chapters targeting host-pathogen interaction at a metabolic level during sepsis pathogenesis, how age affects sepsis pathogenesis and its outcome in old-age population as compared to young population, sepsis-associated acute organ injury mainly targeting acute kidney injury in sepsis, and kallistatin as host-derived immunomodulatory mechanism during sepsis, along with developments in techniques required for early diagnosis of sepsis and sepsis-associated encephalitis, a devastating medical condition observed during severe sepsis. The book is written by experts in their fields associated with sepsis, a critical condition needing great medical attention.